KORELASI ANTARA SIKAP BAHASA DAN KEMAHIRAN MERESPON BAHASA KAIDAH BAHASA INDONESIA PARA GURU BAHASA INDONESIA TINGKAT SMP DI MEDAN - Nur Elide (Balai Bahasa Kalimatan Selatan, 2018)
This research is conducted on the basis of the importance of factors to respond to the rules of the language in supporting the effectiveness of the achievement of Indonesian language proficiency on educators. This research is conducted to prove whether there is a correlation between the activities of responding to the language rules with the language skills on the teacher of junior high school level. This research uses correlational quantitative approach. With the number of respondents 70 educators. Data collection activities were conducted using (1) questionnaires in the form of questions about language rules and (2) Indonesian language proficiency test. From the results of correlation coefficients with SPSS program data analysis process about the correlation between the proficiency of responding the rules of language with the language skills of Indonesia by using the formula of multiple correlation coefficient (multiple corelation). Correlation of proficiency respond to Indonesian rule with correlation attitude of language of educator level junior high school in Medan that is equal to 0,221. The value of 0.221 shows a weak correlation between the proficiency of responding to Indonesian rules with the correlation of language attitudes of junior high school educators in Medan City Still weak.